2020
DOI: 10.20396/joss.v9i00.14958
|View full text |Cite
|
Sign up to set email alerts
|

Visual and auditory cues of assertions and questions in brazilian portuguese and Mexican Spanishy

Abstract: The aim of this paper is to compare the multimodal production of questions in two different language varieties: Brazilian Portuguese and Mexican Spanish. Descriptions of the auditory and visual cues of two speech acts, assertions and questions, are presented based on Brazilian and Mexican corpora. The sentence “Como você sabe” was produced as an yes-no (echo) question and an assertion by ten speakers (five male) from Rio de Janeiro and the sentence “Apaga la tele” was produced as a yes-no question and an asser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 28 publications
(40 reference statements)
2
8
0
Order By: Relevance
“…Since Miranda et al (2019) concluded that both channels are integrated during speech perception of BP wh-question and wh-exclamations with listeners benefiting from the presentation of stimuli with congruent auditory and visual cues, in this paper, the research question and hypothesis of this study are: Will the mismatched facial and audio cues allow the recognition of the speech acts? We hypothesize, based on previous studies, that the incongruent stimuli will hinder the identification of the pragmatic meaning expressed in the auditory modality by intonation, although the comprehension of the speech act will still be possible.…”
Section: Previous Studies On Congruent and Incongruent Modalitiesmentioning
confidence: 96%
See 4 more Smart Citations
“…Since Miranda et al (2019) concluded that both channels are integrated during speech perception of BP wh-question and wh-exclamations with listeners benefiting from the presentation of stimuli with congruent auditory and visual cues, in this paper, the research question and hypothesis of this study are: Will the mismatched facial and audio cues allow the recognition of the speech acts? We hypothesize, based on previous studies, that the incongruent stimuli will hinder the identification of the pragmatic meaning expressed in the auditory modality by intonation, although the comprehension of the speech act will still be possible.…”
Section: Previous Studies On Congruent and Incongruent Modalitiesmentioning
confidence: 96%
“…In the last few decades, a substantial number of multimodal studies analyzed several functions expressed by intonation, such as demarcation (phrasing the speech stream into smaller units), highlighting (the place of prominence within an utterance) and the distinction of sentence mode (statements, questions, requests, commands etc.). For instance, regarding yes-no/echo questions and assertions, due to their essential function as building blocks in conversation (Holler et al, 2018), these speech acts are vastly explored in a multimodal approach in several languages such as Swedish (House, 2002), American English (Srinivasan & Massaro, 2003), British English (Fisher, 1969), Catalan (Borràs-Comes & Prieto, 2011), Mexican Spanish (Gomes da Silva, 2019; Miranda et al, 2020a), Brazilian Portuguese (henceforth BP) (Miranda et al, 2021;Peres et al, 2011) and European Portuguese (Cruz et al, 2017). Overall, these studies support that different facial expressions participate in the transmission of pragmatic meaning conveyed by intonation and that visual cues are perceptually integrated with auditory cues, meaning that listeners benefit from prosodic functions presented in a bimodal condition.…”
Section: Multimodal Communicationmentioning
confidence: 99%
See 3 more Smart Citations